Examining the Examiners: SEC Error Detection Rates and Human Capital Allocation - Kubic, Matthew (The Accounting Review, 2021)
ABSTRACT The ability to detect misreporting is an important aspect of financial reporting regulation. I derive a measure of SEC error detection rates using information from comment letter reviews. Conditional on the SEC issuing a comment letter, I find that the review team detects an error resulting in a restatement in 4.6 percent of cases, while firms eventually restate financial reports for 13.6 percent of periods under review. My measure of SEC error detection rates is the ratio of reviews that detect an error to total reviews that could have detected an error. I document a positive association between detection rates and review team size. Using a novel approach to identify examiner characteristics, I show that this association is driven by the number of accountants on the review team. I find an economically insignificant association between individual examiner performance and economic or career incentives. JEL Classifications: G18; M41; M48. Data Availability: The examiner characteristics data used in this study are available upon request. All other data are available from the sources cited in the text.